Análise histológica do tecido pulpar de ratos com deficiência de testosterona submetidos à movimentação dentária induzida - Machado, Michael Aparecido (2020)
Considering the increased demand for orthodontic treatments in adult and elderly patients, with possible hormonal changes due to age, it is necessary to substantiate orthodontic clinical conduct through histological evaluations. Thus, the present study evaluated histologically how pulp changes in molar of rats with testosterone deficiency that occurred with induced tooth movement, defining a better understanding of the biological aspects of the pulp. 32 Wistar rats separated into four experimental groups were used, with 8 animals in each: G1 - animals in the control group, without experimental manipulation; G2 - composed of animals submitted to bilateral orchidectomy; G3 - animals submitted to the technique of induced tooth movement (MDI) and G4 - constituted by castrated animals submitted to MDI. For the induction of MDI, a nickel-titanium (NiTi) spring was used, exerting a 50cN magnitude force on the upper first molar. Seven days after the installation of the MDI device, the animals were euthanized, the jaws were dissected and fixed in 10% formalin for 24 hours and then processed by routine histological techniques, included in Paraplast, sectioned at 7 um and stained with hematoxylin and eosin for performing pulp analysis under optical microscopy. The efficiency of the force and the proof of tooth movement was evaluated by measuring the distance between the first and second molars, at the level of the cemento-enamel junction. The groups were evaluated histologically for the pattern of cellularity, presence of dystrophic and hemodynamic changes in the dental pulp. The installation of the MDI device was effective in inducing tooth movement in animals in groups G3 and G4, which differed from each other, with a higher rate of movement in the group submitted to castration associated with MDI (G4). Histologically, in the comparative analysis between groups, the pulp of animals from groups G1 and G2, groups that were not moved, presented histological characteristics typical of pulp tissue normality. No dystrophic changes were observed, such as necrosis, fibrosis, nodules or calcifications in the pulp of experimental animals that could be attributed to MDI. The animals with orthodontic movement, castrated or not, presented dilated and congested vessels, in addition to hyalinized vessels in the root and coronary pulp. However, there were no histological changes that could be attributed to testosterone deficiency. Thus, it can be concluded that, in the experimental model used in the present study, testosterone deficiency did not generate morphological and degenerative changes in the pulp during tooth movement. The vascular changes observed in animals result from the orthodontic process and are reversible.